2021
DOI: 10.1186/s12911-021-01560-4
|View full text |Cite
|
Sign up to set email alerts
|

The future of medical scribes documenting in the electronic health record: results of an expert consensus conference

Abstract: Background With the use of electronic health records (EHRs) increasing and causing unintended negative consequences, the medical scribe profession has burgeoned, but it has yet to be regulated. The purpose of this study was to describe scribe workflow as well as identify the threats and opportunities for the future of the scribe industry. Methods The first phase of the study used ethnographic methods consisting of interviews and observations by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…First of all, overloading medical assistants beyond their capacity should be considered. 6,7 According to the present study, physicians are not willing to allow task shifting in all medical clerical tasks. Because the questionnaire did not ask about the factors that led them to each answer, it is still unclear why general physicians consider that ordering prescriptions and examinations, writing medical records and reply letters to referral physicians are chores that they should continue to perform on their own.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…First of all, overloading medical assistants beyond their capacity should be considered. 6,7 According to the present study, physicians are not willing to allow task shifting in all medical clerical tasks. Because the questionnaire did not ask about the factors that led them to each answer, it is still unclear why general physicians consider that ordering prescriptions and examinations, writing medical records and reply letters to referral physicians are chores that they should continue to perform on their own.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, the reasons for the difficulties in shifting medical administrative jobs from physicians to medical assistants need to be discussed. First of all, overloading medical assistants beyond their capacity should be considered 6,7 . According to the present study, physicians are not willing to allow task shifting in all medical clerical tasks.…”
Section: Discussionmentioning
confidence: 88%
“…These may include improving efficiency in the practice environment to shorten the work day (eg, optimized patient rooming/checkout workflows, decreasing operating room turnaround times, and better team-based care), efforts to reduce after-hours electronic health records task burden through the use of documentation assistance (eg, team-based documentation, medical scribes, or artificial intelligence approaches) and optimized inbox management (eg, team-based inbox management or artificial intelligence approaches). [53][54][55][56] Careful attention to ensure equitable scheduling (ie, call schedule or weekend duty), providing coverage for time away, offering less than full-time work options, more optimal family leave policies, and increasing scheduling flexibility can also be helpful. [57][58][59][60][61] More creative approaches to provide assistance with home tasks to enable physicians to attend to high work demands and preserve time for personal relationships have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these cross-training solutions may be more feasible in private practices than in academic institutions but are worth considering. Another significant challenge for support staff and physicians is data entry into the electronic health record; numerous studies have demonstrated the benefits of incorporation of medical scribes into both private and academic practices (7)(8)(9). Finally, it will be imperative that institutions address parity for nurses and technicians so that their compensation is akin to operating room personnel (Table 1).…”
Section: Staffingmentioning
confidence: 99%